2015
DOI: 10.1097/aud.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Degree of Hearing Loss on Auditory Brainstem Response Predictions of Behavioral Thresholds

Abstract: Objectives: Diagnosis of hearing loss and prescription of amplification for infants and young children require accurate estimates of ear- and frequency-specific behavioral thresholds based on auditory brainstem response measurements. Although the overall relationship between ABR and behavioral thresholds has been demonstrated, the agreement is imperfect, and the accuracy of predictions of behavioral threshold based on ABR may depend on degree of hearing loss. Behavioral thresholds are lower than ABR thresholds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
0
34
1
Order By: Relevance
“…Electrophysiologic testing, such as an auditory brainstem response (ABR), is considered an essential piece of diagnostic testing for infants and children who are not yet able to complete behavioral testing. 58 Research by McCreery et al 59 reconfirmed that ABR thresholds are a strong predictor of a child's behavioral thresholds; however, the amount of accuracy between the ABR thresholds and behavioral thresholds depends on the degree of hearing loss. For infants who have a severe-to-profound hearing loss, a potential exists for the accuracy of their ABR thresholds to be poorer.…”
Section: Potential For Poorer Accuracy Of Abr Thresholds For Infants mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiologic testing, such as an auditory brainstem response (ABR), is considered an essential piece of diagnostic testing for infants and children who are not yet able to complete behavioral testing. 58 Research by McCreery et al 59 reconfirmed that ABR thresholds are a strong predictor of a child's behavioral thresholds; however, the amount of accuracy between the ABR thresholds and behavioral thresholds depends on the degree of hearing loss. For infants who have a severe-to-profound hearing loss, a potential exists for the accuracy of their ABR thresholds to be poorer.…”
Section: Potential For Poorer Accuracy Of Abr Thresholds For Infants mentioning
confidence: 99%
“…According to McCreery et al, 59 ABR thresholds often underestimate the hearing loss for individuals who have a moderate or greater degree of hearing loss. To account for differences between ABR threshold and behavioral threshold for individuals with greater degrees of hearing loss, a frequency-specific correction factor was developed.…”
Section: Potential For Poorer Accuracy Of Abr Thresholds For Infants mentioning
confidence: 99%
“…Auditory brain stem responses are far-field potentials that measure all ranges of the early auditory evoked potentials (AEP) using signal averaging [52,53]. It consists of a series of seven waves (I-VII.)…”
Section: Auditory Brain Stem Responses (Abr)mentioning
confidence: 99%
“…Neural responses during an auditory brainstem response test (ABR) are generated subcortically by the auditory nerve and subsequent brain stem fiber tracts and nuclei. Using either click or chirp stimuli is still the gold standard for electro-physiologically assessing the integrity of the auditory nerve and the brain stem pathways as they lead the electrical stimuli towards the cortex [52][53][54][55] ( Figure 1C and D). Neuronal junction points in the brainstem as generator relay structures are identified in the form of waves on the electrophysiological recordings in normal subjects ( Figure 1C); while these points are not registered in patients with a profound hearing loss (Figure 1D).…”
Section: Examination Of Patients Expecting Cochlear Implantationmentioning
confidence: 99%
“…Despite there being no universally adopted method to define nHL, ABR thresholds in dB nHL are highly and positively correlated with pure-tone behavioral hearing thresholds in dB HL (Stapells et al, 1995;Gorga et al, 2006;Vander Werff et al, 2009;McCreery et al, 2015). For example, McCreery et al (2015) found correlations .0.87 while Stapells et al (1995) found correlations .0.93 between ABR and behavioral hearing thresholds in children.…”
Section: Differences Between Abr and Behavioral Threshold Measuresmentioning
confidence: 99%